Publicly Available Anatomic Total Shoulder Arthroplasty Rehabilitation Protocols Show High Variability and Frequent Divergence from the 2020 ASSET Recommendations - Nabil Mehta; Alexander J Acuna; Johnathon R McCormick; William E Harkin; Hasani W Swindell; Steven F Defroda; Mike Reinold; Gregory P Nicholson; Grant E Garrigues (North American Sports Medicine Institute, 2024)
# Background In 2020, the American Society of Shoulder and Elbow Therapists (ASSET) published an evidence-based consensus statement outlining postoperative rehabilitation guidelines following anatomic total shoulder arthroplasty (TSA). # Purpose The purpose of this study was to (1) quantify the variability in online anatomic TSA rehabilitation protocols, and (2) assess their congruence with the ASSET consensus guidelines. # Methods This study was a cross-sectional investigation of publicly available, online rehabilitation protocols for anatomic TSA. A web-based search was conducted in April 2022 of publicly available rehabilitation protocols for TSA. Each collected protocol was independently reviewed by two authors to identify recommendations regarding immobilization, initiation, and progression of passive (PROM) and active range of motion (AROM), as well as the initiation and progression of strengthening and post-operative exercises and activities. The time to initiation of various components of rehabilitation was recorded as the time at which the activity or motion threshold was permitted by the protocol. Comparisons between ASSET start dates and mean start dates from included protocols were performed. # Results Of the 191 academic institutions included, 46 (24.08%) had publicly available protocols online, and a total of 91 unique protocols were included in the final analysis. There were large variations seen among included protocols for the duration and type of immobilization post-operatively, as well as for the initiation of early stretching, PROM, AROM, resistance exercises, and return to sport. Of the 37 recommendations reported by both the ASSET and included protocols, 31 (83.78%) were found to be significantly different between groups (p\<0.05). # Conclusion Considerable variability was found among online post-operative protocols for TSA with substantial deviation from the ASSET guidelines. These findings highlight the lack of standardization in rehabilitation protocols following anatomic TSA. # Level of Evidence 3b